A Nonclassical Monocyte Phenotype in Peripheral Blood is Associated with Nonalcoholic Fatty Liver Disease: A Report from an EMIL Subcohort - Wang, Y.; Oeztuerk, S.; Kratzer, W.; Boehm, B. O.; for the EMIL-Study Group (Hormone and Metabolic Research, 2016)
Nonalcoholic fatty liver disease (NAFLD) as the prototypic hepatic manifestation of metabolic syndrome is an independent risk factor for cardiovascular disease. Our study was designed to investigate the association between NAFLD and alteration in monocyte subsets as hallmark of cardiovascular disease. Seventy-three “Echinococcus Multilocularis and other medical diseases in Leutkirch” (EMIL) population-based cohort participants (mean observation period 11 years) were selected to study their monocyte phenotype by multiparameter flow cytometry. NAFLD was diagnosed using standard ultrasound based criteria excluding other causes of fatty liver disease. Three monocyte subsets (“classical” CD14++ CD16–, “intermediate” CD14++  CD16+, “nonclassical” CD14+CD16++  monocytes), and surface markers (CD36 and CD9) were determined. Classical risk markers covering inflammatory and dysmetabolic characters were also determined. Forty-three out of 73 subjects revealed a stable clinical phenotype, namely 17 subjects revealed NAFLD, whereas 26 subjects showed no fatty liver disease. Compared to the nonfatty liver group, the nonclassical monocyte fraction (p=0.049), total monocyte fraction and count were increased in NAFLD probands (p=0.028, and 0.035, respectively), while classical monocyte fraction (p=0.034) was decreased. Total monocyte fraction, nonclassical monocyte fraction, and waist circumstance were independent risk factors for NAFLD. The nonclassical monocyte fraction and classical monocyte fraction were significantly correlated with waist-to-hip ratio. This pilot long-term follow-up study suggests that nonclassical monocyte fraction and total monocyte fraction might have potential as a prognostic and modifiable biomarker in NFALD patients. This novel marker set might therefore be of interest to monitor druggable inflammatory pathways in individuals with hepatic manifestation of the metabolic syndrome.
Keywords: biomarker; monocyte subsets; NAFLD; metabolic syndrome; cardiovascular disease